The Relationship between Emotional Intelligence and Job Performance of Call Centre Agents - Noorazzila Shamsuddin; Ramlee Abdul Rahman (2014)
This study attempted to investigate the relationship between emotional intelligence and job performance of call centre agents. Two call centres located at Kuala Lumpur were selected as the subject of this study involving 118 respondents. The self-report emotional scale developed by Wong & Law (2002) known as Wong and Law Emotional Intelligence Scale (WLEIS) had been adapted as the measurement for the level of EI among the call centre agents. All the items in the independent and dependent variables were tested through reliability test to ensure the reliability of the scale. The correlational analysis was carried out and the result indicated there was a relationship between EI and job performance. Hence, multiple regression analysis was conducted to examine the variance in dependent variable through independent variable by giving the relative contribution of each independent variable. The findings of the study indicated there was significant relationship between emotional intelligence and job performance. Moreover, two EI dimensions contributed to job performance, namely regulation appraisal emotion (RAE) and use of emotion (UOE). Analysis of the moderator variable, indicated gender did not affect the relationship between the independent variable (EI) and dependent variable (Job performance).